Poplar tree (Populus balsamifera L.) as indicator of mercury emission from a point source; Chemosphere; Vol. 287 - Yusupov D. V. Dmitry Valerievich; Lyapina E. E. Elena Evgenievna; Tursunalieva E. M. Elena Muratovna; Osipova N. A. Nina Aleksandrovna; Baranovskaya N. V. Nataliya Vladimirovna (2022, 2022)
Title screen